The difference of Use of CT in the general versus pediatric emergency departments for adolescent patients in the same tertiary hospital - Kim, Seul Ki; Jung, Jin Hee; Lee, Jin Hee; Jung, Jae Yun; Kwon, Hyuksool; Paek, So Hyun; Kwak, Young Ho; Kim, Do Kyun (Clinical and experimental emergency medicine, 2019)
The use of computed tomography (CT) in pediatric patients has decreased since the association between radiation and cancer risk has been reported. However, in adolescent patients being treated as adult patients, there has been a high incidence of CT use in emergency departments (EDs). Thus, this study aimed to evaluate the CT use in adolescent patients with complaints of headache or abdominal pain in the general and pediatric EDs of the same hospital. A retrospective chart review of patients aged 15 to 18 years, who presented with headache or abdominal pain at the general and pediatric EDs of Seoul National University Hospital from January 2010 to December 2014, was conducted. A total of 407 adolescent patients with complaints of headache and 980 with abdominal pain were included in this study. The adolescent patients in the general ED were more likely to undergo CT scans than those in the pediatric ED, with both patients having headache (42.4% vs. 20.5%, respectively, P<0.001) and abdominal pain (29.0% vs. 18.4%, respectively, P<0.001). There was no statistical difference in the rates of positive CT findings between the general and pediatric EDs. The frequency of visits to the general ED was associated with high rates of CT use in adolescent patients with complaints of headache (odds ratio, 3.95; 95% confidence interval, 2.01 to 7.77) and those with abdominal pain (odds ratio, 1.76; 95% confidence interval, 1.18 to 2.64). The ED setting influences the use of CT on adolescent patients, and a child-friendly environment could reduce the radiation risks.